Effect of Soaking Tawes Fish Eggs (Barbonymus gonionotus) in Tea Solution (Camellia sinensis) on the Hatchability and Survival of Larvae - Puspitasari, Ika; Hastuti, Sri; Sarjito, Sarjito; Nurlatifah, Annisa Oktafianti (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2025)
Tawes fish (Barbonymus gonionotus) is one of the fish with high production demand, but seed production is still low. One of the obstacles is fungal attacks. An alternative to overcome fungal attacks in the hatching phase of fish eggs is to use one of the plants that is anti-fungal. One alternative ingredient that is safe and can be used in controlling fungi is using tea. The active compounds of flavonoids, tannins, saponins found in tea are expected to be natural alternative ingredients for anti-fungals. This study aims to determine the effect and optimum concentration of tea solution (C. sinensis) on the hatching power and survival rate of tawes fish larvae (B. gonionotus). This study was conducted in April 2023 at the UPT Balai Benih Ikan Pandak Banyumas, Central Java. The method used was an experiment with a Completely Randomized Design (CRD) with 4 replications and 5 replications each. The hatching media was added with tea solution (C. sinensis) with concentrations A (0 g/l), B (3 g/l), C (6 g/l), and D (9 g/l). The data observed included the length of egg hatching time, yolk absorption time, egg hatchability (HR), survival rate (SR), and water quality. The results showed that soaking eggs in tea solution affected the hatching power of eggs and the survival of tawes fish larvae. The results of the hatching rate values in succession from treatments A to D were 64.00 ± 4.18a%, 81.00 ± 4.18c%, 85.00 ± 3.54c% and 71.00 ± 4.18b%, while the results of the survival rate values in succession from treatments A to D were 62.47 ± 3.15a%, 75.41 ± 9.46bc%, 79.90 ± 3.86c%, and 67.56 ± 6.33d). The optimum dose of soaking tawes fish eggs in tea leaf solution for the hatching power of eggs and the survival of tawes fish larvae was 4.96 - 4.98 g / l.